HUBUNGAN DUKUNGAN KELUARGA TERHADAP PERAWATAN KAKI UNTUK MENCEGAH KAKI DIABETIK PADA PASIEN DM TIPE 2 DI RSUD UNGARAN - Ismonah Ismonah; Anita Putri Octaviani (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2019)
Diabetes Mellitus (DM) is one of the chronic diseases that can cause various complications, one of which is diabetic foot wounds. In minimizing these complications, there is a need for adherence from DM patients to perform foot care. One that plays a role in influencing the adherence of DM patients to foot care is family support. This study aims to determine the relationship of family support for foot care to prevent diabetic foot in type 2 DM patients in Ungaran Hospital. The method used was cross sectional, with 30 respondents determined by purposive sampling technique. The results showed good family support as many as 18 respondents (60%) and enough foot care as many as 23 respondents (76.7%). The results of the Fisher test showed an association of family support for foot care in type 2 DM patients in Ungaran Hospital with (p value = 0.001). Based on the results of the study, it is expected that nurses in hospitals can involve families in improving the behavior of patients in doing foot care and increasing knowledge about DM in patients and families. Keywords: family support, foot care, type 2 DM